UJI ANTIHIPERTENSI KOMBINASI EKSTRAK HERBA SELEDRI, DAUN KUMIS KUCING DAN BUAH MENGKUDU PADA TIKUS GALUR SPRAGUE DAWLEY NORMAL DAN HIPERTENSI - Rumiyati Rumiyati; Arif Rahman Hakim; Arini Dwi Winarti; Dea Nurma Septia (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Seledri (Apium graviolens L.), kumis kucing (Orthosiphon stamineus Benth.), and mengkudu (Morinda citrifolia L.) have been used to treat hypertension diseases in Indonesia. Previous researches have been done to determine antihypertensive activity of extracts of the sample in single extract. However, there are limited studies on effect of the extracts on a combination of three samples. This research was therefore aimed to study the effect of the combination on lowering blood tension on normotensive and spontaneously hypertensive rats. Non Invasive Blood Pressure technique equipped with Non Invasive Blood Pressure System (CODA®) was used to measure effect of extracts on antihypertensive activity. Sprague Dawley rats were divided into 2 groups (normotensive and spontaneously hypertensive rats using fenilefrin) and treated with combination extracts in doses of 20.25 and 40.5 mg/kg BW of rats. The result showed that the combined extracts can decrease in blood pressure of both two of the groups. Normotensive group of the rats treated at doses of 20,25 and 40,5 mg/kg BW of rats had lower persentase of systolic blood pressure as much as 7,1 ± 1,8 % and 10,2 ± 2,6 %, whilst percentage of diastolic blood pressure had lower percentage as much as 13,8 ± 3,2 % and 12,3 ± 3,1 %, respectively. Furthermore, spontaneously hypertensive rats treated at doses of 20,25 and 40,5 mg/kg BW of rats also showed lower systolic blood pressure as much as 16,10 ± 0,90 % and 15,84 ± 1,55 % and diastolic blood pressure as much as 19,48 ± 1,03 % and 17,77 ± 1,34 %. These results suggest that administration of combination of three extracts exhibited antihypertensive in both of the rat groups.